Solar water heater / Azizi Abdullah - Abdullah, Azizi (1996)
As a traditional sources become more scare, it is only natural for us to look upward, to the sun, for an alternative sources of energy. The sun is largely responsible for almost all of our conventional energy sources. Photosynthesis of plant and algae supported ancient life that later become fossils fuels. Even hydroelectric power would not be possible without the evaporation of water. Yet solar energy itself has not been fully accepted as safe, efficient, and understandable energy source. Until recently the unrestricted availability and low cost of traditional energy source have precluded much practical application of solar energy. The time has come, however, for all of us to become more aware of the direct contributions solar energy can make to our lives and our economy.